Analisis Aerodinamika Diffuser Dengan Kurvatur Lengkung Berbasis Airfoil Pada Variasi Sudut Serang dan Tinggi Flange - Muhammad, Baginda Arsyi; Wiratama, I Kade; Joniarta, I Wayan (CV. IRA PUBLISHING, 2025)
Low wind speeds in residential areas often pose an obstacle to the use of small- and micro-scale wind turbines. Various efforts have been made to address this issue, particularly to improve wind turbine performance. One such method is the application of a diffuser, or wind lens, during turbine operation. However, existing diffuser designs still require further development in order to achieve more efficient aerodynamic performance, optimize wind speed, and provide a more compact configuration. In this study, a diffuser with curved geometry based on the Wortmann FX-63-137 airfoil was analyzed using Ansys Fluent simulations. The variations tested included angles of attack of 0°, 4°, 8°, and 12°, as well as flange heights of 0.05D, 0.10D, 0.15D, 0.20D, and 0.25D. The simulation results indicated an increase in wind velocity at the throat area, with the best performance achieved at a 4° angle of attack with a 0.10D flange. Under these conditions, the available wind power reached 203.20 W, representing an increase of approximately 34.01%.